2021
DOI: 10.22541/au.161058060.07089740/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Sinus Rhythm Maintenance on Major Adverse Cardiac and Cerebrovascular Events after Catheter Ablation of Atrial Fibrillation: Insights from AF Frontier Ablation Registry

Abstract: Introduction: The impact of catheter ablation for atrial fibrillation (AF) on cardiovascular events and mortality is controversial. We investigated the impact of sinus rhythm maintenance on major adverse cardiac and cerebrovascular events after AF ablation from a Japanese multicenter cohort of AF ablation. Methods and Results: We investigated 2737 consecutive patients (25.6% female, mean age 63.4 ± 10.3 years) who underwent a first catheter ablation for AF from the Atrial Fibrillation registry to Follow the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, the influence mechanism of cortisol on the closure of the arterial catheter is unclear (17). Animal experiments have shown that cortisol can reduce prostaglandin synthesis by inhibiting phospholipase A, and can reduce the sensitivity of the arterial catheter to the prostaglandin expansion effect (18,19). Studies have also found that cortisol itself has a weak contractile effect on the artery (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence mechanism of cortisol on the closure of the arterial catheter is unclear (17). Animal experiments have shown that cortisol can reduce prostaglandin synthesis by inhibiting phospholipase A, and can reduce the sensitivity of the arterial catheter to the prostaglandin expansion effect (18,19). Studies have also found that cortisol itself has a weak contractile effect on the artery (20).…”
Section: Discussionmentioning
confidence: 99%
“…According to the Japanese multicenter cohort study of patients with AF after catheter ablation, freedom from AF recurrence after catheter ablation was independently associated with a lower risk of cardiac adverse events or death. 13 Reducing AF burden by successful catheter ablation may improve the adverse hemodynamic state, leading to a reduced risk of heart failure or cardiovascular death in the AF population. In the present study with HFmrEF and HFpEF, the incidence of cardiovascular death or hospitalization for index at rest.…”
Section: Importance Of Successful Sinus Rhythm Maintenance After Cath...mentioning
confidence: 99%